2018
DOI: 10.32532/jori.v6i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Respon Radiasi dan Kesintasan Karsinoma Nasofaring Stadium Lanjut Lokal di Departemen Radioterapi Rumah Sakit Cipto Mangunkusumo Periode Januari 2007-Desember 2011

Abstract: Penelitian ini bertujuan untuk mengetahui respon radiasi, kesintasan hidup, dan faktor yang mungkin mempengaruhi dalam penanganan karsinoma nasofaring stadium lanjut lokal. Penelitian ini merupakan penelitian retrospektif deskriptif analitik terhadap 391 pasien karsinoma nasofaring stadium lanjut lokal yang berobat di Departemen Radioterapi RSCM periode Januari 2007-Desember 2011. Respon radiasi dianalisa menggunakan uji korelasi Spearman dan analisis kesintasan dihitung dengan kurva Kaplan Meier pada pasien y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
2
2
Order By: Relevance
“…The most common clinical stage in our sample was IVA (53.98%). These results differ from an earlier study in Jakarta that showed the most common stage to be IVB (32.7%) [ 6 ]. Studies in Hong Kong by Lee et al and Turkey by Topkan et al have reported the most prevalent stage to be III (68.24% and 56.4%) [ 4 , 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The most common clinical stage in our sample was IVA (53.98%). These results differ from an earlier study in Jakarta that showed the most common stage to be IVB (32.7%) [ 6 ]. Studies in Hong Kong by Lee et al and Turkey by Topkan et al have reported the most prevalent stage to be III (68.24% and 56.4%) [ 4 , 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The histopathological characteristics of patients in Indonesia are the same as those in China [ 4 ] (90% WHO type III), which is chemoradiosensitive, but differ in terms of survival. In this study, the three-year mortality rate was 40.14%, which is better than in earlier studies conducted in Jakarta [ 6 ] and Yogyakarta [ 5 ] at which time, the rates were 47.1% and 70%, respectively. A study in China revealed a mortality rate of 22% [ 4 ].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations